(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article provides a comprehensive analysis of gender dynamics in the scientific sphere of Central Asia (Uzbekistan, Kazakhstan, Kyrgyzstan, Tajikistan, and Turkmenistan). The study focuses on institutional constraints and sociocultural factors that hinder the professional development of women researchers. It examines the phenomenon of the “double burden” and explores cross-country comparative differences. The article also discusses the dynamics of reforms implemented within the framework of international conventions (CEDAW) and national strategies. The research draws on data from the World Bank, UNICEF, DataReportal, official national statistical sources, as well as comparative findings from diverse scholarly literature.